Antibacterial effect of two novel sealants: A laboratory-based study - Dipali D Deshpande; Dirgham Maniar; Ankita Bhargava; Parinika T Joshi; Ravi Kadur Sundar Raj; Alok Dubey (Wolters Kluwer Medknow Publications, 2024)
Background: This research sought to assess the impact of polyhexamethylene guanidine hydrochloride (PHMGH) and 1,3,5-triacryloyl hexahydro-1,3,5-triazine (TAT) on the antibacterial activity of an experimental resin sealant. Materials and Methods: The two experimental sealants were formulated based on previous research, and Streptococcus mutans (S. mutans) was tested for biofilm and planktonic bacteria's antibacterial properties. In 48 hours, 300 L of frozen S. mutans in skim milk was stored in an oven at 37°C in a microaerophilic atmosphere with 5% of CO2 and put on a petri plate containing brain-heart infusion (BHI) broth with agar at 15 g/L. By combining 100 mL of the subculture broth with 900 mL of a sterile saline solution (0.9%) in an Eppendorf tube, the initial inoculum used for the experiments was evaluated. The colonies were measured in colony-forming units per milliliter (CFU/mL) after being counted visually. To measure the antibacterial activity, log CFU/mL was used to express the number of bacteria in the broth that had been in contact with the samples for 24 hours. Results: Outcomes of antibacterial activity against planktonic bacteria and against biofilm development on polymerized materials. The two innovative sealant materials were found to differ significantly from one another, while group 2's mean and standard deviation values were larger. Conclusion: Dental sealants designed with PHMGH and TCPTAT for anticaries application showed less bacterial growth throughout time the cavity prevention properties of the resin sealant.